(untitled) (GEON Journal (Management, Organizations and Business), 2014)
This article highlights the importance of changing traditional thinking by a creative mind as a management tool to direct a company to train leaders with motivation, people who have the ability to contextualize the multiple intelligences of a work team and identify skills of each and generate thoughts from a critical context.